Two Deficits and Economic Growth: Case of CEE Countries in Transition - Gurgul, Henryk; Lach, Łukasz (Managerial Economics, 2012)
The main goal of this contribution was to provide evidence on the dynamic interdependencies between economic growth and budget and trade deficits in ten new EU members in transition in the last decade. It is worth to note, that besides establishing directions of causal relationships this paper also derived some suggestions on signs of the dynamic dependencies analyzed. Outcomes of this paper confirmed that the budget deficits were significantly slowing down the GDP growth rates in case of new EU-members in transition. In addition, these deficits had negative impact on the convergence process of examined countries towards the highly developed European economies. The evidence supporting adverse causality was considerably weaker. The empirical results allow to claim that in the period under study there was a unidirectional negative Granger causality from budget deficits to trade deficits. Therefore, in case of CEE economies in transition the twin deficit hypothesis was not the case.